2009
DOI: 10.1007/s10926-009-9196-x
|View full text |Cite
|
Sign up to set email alerts
|

Work Related Risk Factors for Neck, Shoulder and Arms Complaints: A Cohort Study Among Dutch Computer Office Workers

Abstract: Introduction This study aims to investigate the relationship between work-related physical and psychosocial characteristics and complaints of the neck, shoulder and forearm/hands. Methods Data were used from a prospective Dutch cohort study among computer office workers with a follow-up period of 2 years. The study was conducted among 264 computer users. Physical and psychosocial risk factors were tested to predict the occurrence of neck, shoulder and forearm/hands complaints. Bivariate and multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
108
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(134 citation statements)
references
References 34 publications
12
108
0
9
Order By: Relevance
“…The results showed a correlation between the execution of difficult tasks in the workplace and the occurrence of symptoms in the neck and shoulders. These results are consistent with other prospective studies in which the jobs requirements were shown as risk factors in the occurrence of pain in the neck area (Eltayeb et al, 2009;Ariens, Bongers, Hoogendoorn, van der Wal& van Mechelen, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed a correlation between the execution of difficult tasks in the workplace and the occurrence of symptoms in the neck and shoulders. These results are consistent with other prospective studies in which the jobs requirements were shown as risk factors in the occurrence of pain in the neck area (Eltayeb et al, 2009;Ariens, Bongers, Hoogendoorn, van der Wal& van Mechelen, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Data show that increased demands of work, reduced opportunity to make decisions, work pressure, increased exertion, job dissatisfaction, and lack of social support from colleagues and superiors are important risk factors for the occurrence of upper limb disorders (Eltayeb, Staal, Hassan, & de Bie, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, musculoskeletal symptoms are not restricted to occupations with high physical demands but are also found in predominantly sedentary occupations (6). Data from health insurance providers clearly show the consequences of abnormal and excessive biomechanical stress across the whole working population.…”
mentioning
confidence: 99%
“…According to a national survey of the Japan Ministry of Health, Labour and Welfare, Japanese laborers who engaged in VDT-related work comprised only 15.3% of all the working population in 1998, but after 10 years, that fraction increased to 79.2% 1) . German census data from 2004 suggested that twenty-one million people, comprising 59% of all hired workers, were engaged in computer-related work during daily life 2) . Along with the rapid changes of working environments into VDT stations, various symptoms related to VDT use have been increasingly reported.…”
mentioning
confidence: 99%